Groundwater Geochemistry in Aquifers in An Giang, Vietnam - Van Tuc, Dang; Quang Khai, Ha; Le Phu, Vo (VNU Journal of Science: Earth and Environmental Sciences; Vol 42 No 1DO - 10.25073/2588-1094/vnuees.5223, 2025)
Groundwater plays a vital role in the lives of people and ecosystem. In An Giang province located in the Mekong Delta, groundwater contributes significantly to the domestic water supply and economic development. This study surveyed 142 groundwater samples in An Giang to understand the groundwater geochemical characteristics. The results showed that TDS values of groundwater ranging from 80 to 4,540 mg/L. About 46% of the total 142 samples have TDS > 1,000 mg/L and were not suitable for drinking purpose. Hydrogeochemical facies evolution diagram was applied to investigate salinization and 43% of groundwater samples were impacted by salinization processes. The salinization of groundwater was mainly observed in the upper and upper middle Pleistocene aquifers. In both Holocene aquifer in shallow depth (~ 20 m below land surface) and Pliocene aquifers in very deep depth (>150 m below land surface), groundwater geochemistry indicated freshening condition. The freshening in shallow aquifers was due to recent recharges by rainwater or river system. In the deep aquifers, the freshening process was caused by fossil groundwater in the area. These results highlight the vulnerability of deep fresh aquifers to vertical salinization and underscore the need for improved groundwater protection strategies in the area.